THE ROLE OF PUBLIC POLICY IN MITIGATING CORRUPTION: A COMPARATIVE ANALYSIS OF ANTI-CORRUPTION STRATEGIES IN ASIAN DEMOCRACIES - Z. A., Safrizal; Sari, Avid Leonardo; Limijadi, Edward Kurnia Setiawan; Saliman, Abdul Rasyid; Taufiqurrachman, Taufiqurrachman (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
Corruption is one of the major challenges faced by democracies in Asia, threatening government transparency and accountability. Effective public policies are essential to prevent corrupt practices and strengthen institutional integrity. Various anti-corruption strategies have been implemented, but their effectiveness varies depending on the political, social, and economic contexts of each country. This study aims to analyze the role of public policy in mitigating corruption in democracies in Asia through a qualitative approach. The research method involves collecting data from various relevant sources and comparative analysis of the strategies implemented. The results show that countries with strong legal systems and independent institutions are more successful in tackling corruption. In addition, civil society and media participation also contribute significantly to the effectiveness of anti-corruption policies. On the other hand, developing democracies face various challenges, including elite political influence and resource constraints, which hinder the implementation of anti-corruption policies. Comprehensive reforms are needed to create a more supportive environment for eradicating corruption.gb777